Low frequency impedance and structural properties of high temperature superconducting YBa2Cu3Ox thin films - Murray, Bryan Gerrard (1994)
R.F. sputtering was used to deposit thin films of YBCO onto a variety of substrates. The films were found to be superconducting with critical temperatures in excess of 77 Kelvin. Using x-ray diffraction the orientation of the YBCO thin films on MgO(lOO) was found to be c-axis. The films deposited on SrTiO3(100) were found to be a and c axis orientated, where as on SrTiO3(110) the thin films were (110/013) orientated. Using scanning electron microscopy the films were found to be granular in nature. The films deposited on MgO(lOO) had circular grains. The films deposited on SrTiO3(110) had elongated sausage like grains. The shape of the grains is due to spiral and ridge type growth respectively. Electrical measurements were taken using a 4 probe contact technique. The rf experiments were used to calculate the paraconductivity. The coherence length and superconducting sheet thickness where calculated for c-axis YBCO thin films using the Lawrence-Doniach theory. The coherence length was found to be 4 A, the sheet thickness was 11 A for T=0 Kelvin. Examination of the transition region revealed a flux flow region in films deposited on MgO(lOO). The temperature dependence of the flux flow region was found to be in agreement with that predicted by Kosterlitz-Thouless and independently by Berezinskii. This implies that the films were 2 dimensional in nature. Some films deposited on SrTiO3(110) do not appear to have a flux flow region. Films deposited on SrTiO3(110) may be 3 dimensional. Examination of the magnetic properties were in agreement with existing theory, namely that the resistance was directly proportional to the applied magnetic field. In order to perform critical current measurements the films were wet etched into strips. The temperature dependence of the critical current of the granular thin films was found to be in agreement with Ambegaokar-Baratoff theory for a 2 dimensional film of Josephson junctions. An ac electrical technique was used to investigate the reactive properties of YBCO thin films. Results show that the normal inductance was very anisotropic. The inductance for temperature below Tc was used to calculate the penetration depth. The penetration depth, for T=0K, was found to be between 2.24-10.58[xm. Penetration depths of this magnitude are predicted by Ambegaokar-Baratoff for certain cases. The temperature dependence of the penetration depth was investigated in terms of the London theory and good agreement was found. Anomalous behaviour was found to occur in certain thin films. The anomaly was present as a change in the temperature dependence of the kinetic inductance. The anomaly may be due to 2D-3D crossover, known to occur in YBCO thin films. An anomalous resonance effect was observed in very thin film at 48 Kelvin. The behaviour of the anomaly is very similar to a dielectric but may be due to substrate effect.